Confección de prendas de vestir, línea informal con inspiración en el nevado Chimborazo para niñas de 5 a 11 años y mujeres de 15 a 30 años de edad de la ciudad de Riobamba provincia de Chimborazo en 2016 - Aucacama Zavala, Margarita Beatriz (2016)
The present research work is aimed at the development of new collections of informal style clothing through the applicability of an inspiration that in this case is the Nevado Chimborazo, aimed at girls aged 5 to 11 years and women 15 to 30 years of age of the city Of Riobamba province of Chimborazo It was important to carry out the interaction and active participation of the women of the city of Riobamba province of Chimborazo through the structured surveys that allowed us to know if the project is going to be viable or not, in order to elaborate the new collections of informal clothing of Practical and objective way. The research focused on a scientific approach related to the independent variable that is the inspiration of the snowy Chimborazo, the dependent variable, the informal garment making style. The research work consists of the following information:  It refers to the Theoretical Framework where it begins with a broad approach to the theory to later refer to the new clothing collections.  Corresponds to the Methodological Strategies, which describes the type of research, population, methods, techniques and instruments.  It refers to the analysis and interpretation of results obtained in the research process, ie the survey applied to women in the city of Riobamba province of Chimborazo and the observation made to the environment in which each of them are developed, whose data Were tabulated and processed in tables and statistical graphs to analyze and interpret and finally carry out the verification of the hypothesis.  It corresponds to the proposal, which consisted of a fundamental alternative to solve the problem of creating a new and creative collection of informal style clothing.  The results show that through the use of an inspiration, new collections of informal style clothing can be developed objectively and following each of the methodological stages. It also allows us to put into practice everything we have learned to at some point be able to strengthen the learning of the contents, aimed at improving skills and abilities in the Fashion Design career.